P224 Why Are We Failing in the UK in Non-Invasive Ventilation (NIV) and Acute Exacerbations of COPD (AECOPD)? Review of Our Local Practise. (19th November 2012) - Protheroe, KM; Bentley, R; Sams, TE; Parker, S; Sayers, R; Taylor, J; Killen, JW; Curtis, HJ
Abstract : Introduction and Objectives: Ward based NIV is proven treatment in AECOPD with type II respiratory failure with pH 7.25– 7.35.(1) Increasingly this modality is being used out with the trial evidence. The RCP audit of real world practise showed concerning results: failure or delay to deliver NIV and increaced mortality in NIV-treated patients compared to equally severe patients managed without NIV (26% vs 14%).(2) In light of these factors we reviewed our NIV use across our hospital. Did our local service need improvement? Methods: We audited 4 months of emergency department admissiond in late 2011 to 2012, ward based NIV care in February-March 2011 and February-March 2012 using the BTS audit tool and critical care admissions for AECOPD from January 2010 to Decemeber 2011. Results: Emergency Department: NIV was only considered in 78% of possible patients and only given in 37%. Significant delays were seen in starting NIV; median 357 minutes (range 138–1366). Ward-based NIV: In 2011 overall mortality was 33%, however patients with pH 7.25–7.35 mortality was 11%, matching the landmark trial outcomes.(1) If pH was <7.25 mortality was 80%. In 2012 oxygen toxicity contributed to acidosis is 33% of patients and overall mortality was 40%. Critical Care Department (CCD): Time to respiratory support was a median of 4 hours. 31% of patients required invasive ventilation, this was higher if consolidation was present on CXR (p=0.005). Overall mortality was 20%, significantly higher if pH<7.25 at any time at 35% (p=0.02) and if CXR consolidation was present (25% vs 12.5). Conclusions: Unfortunately NIV is not commenced in all appropriate patients, delays are common place and NIV is being used in severely ill and very acidotic patients with high mortality outcomes. Driven by national audit data, this detailed analysis of our practise has allowed us to drive local changes to improve our service including: 24/7 NIV nurse; early involvement with CCD in appropraite patients with pH<7.25 and re-education of staff across the Trust. References: Plant PK et al. Early use of NIV for AECOPD on general respiratory wards. Lancet 2000 ; 355:1931–35. Roberts CM et al. Acidosis, NIV and mortality in hospitalised COPD exacerbations. Thorax 2011 ; 66:43–48.